A way to limit the long-term degradation of solid oxide fuel cell cathode by decorating the surface with K2NiF4-Structure Pr4Ni3O10+ phase - Saher S.; Tan C.Y.; Ramesh S.; Yap B.K.; Ong B.H.; Mo K.H.; Al-Furjan M.S.H. (Elsevier B.V., 2025)
Prolonged annealing of La0.6Sr0.4Co0.2Fe0.8O3- (LSCF) at 700 C for 1000 h resulted in phase segregation on the surface in the form of submicron-sized SrO on the grains and micron-sized CoFe2O4 particles near the grain boundaries during electrical conductivity relaxation (ECR) measurements. The presence of segregated particles results in a substantial decrease in the surface exchange coefficient, kchem. To mitigate this issue, the LSCF electrodes underwent a systematic coating process with the K2NiF4-structure Pr4Ni3O10+ (PNO), while varying the loading content, thickness, and porosity. This is achieved by adjusting the gap between the nozzle exit and LSCF surface, ranging from 2 cm to 9 cm, coupled with the application of ultrasonic vibration of the nozzle chamber operating between 40 kHz and 180 kHz. Optimal surface coverage with a loading content of 0.28 mg cm?2 referred to as PNO5 results in a significant increase in kchem by up to one and a half order of magnitude compared to bare LSCF. The PNO coating effectively suppresses phase segregation during prolonged exposure, resulting in a substantial decrease in degradation. The improved performance is attributed to the optimal surface coverage of coated particulates, which enhances the active sites for oxygen reduction reaction (ORR) and the triple phase boundary (TPB) area. These exceptional characteristics position PNO coated LSCF as a highly promising cathode option for low temperature solid oxide fuel cells (SOFCs). ? 2023 Elsevier B.V.